Peran Moderasi Perceived Environmental Uncertainty Dan Task Uncertainty Dalam Hubungan Antara Informasi Akuntansi Dengan Kinerja Bisnis - Ika Neni Kristanti (JURNAL EKONOMI DAN TEKNIK INFORMATIKA, 2019)
The aims of this study are to analyze the effect of accounting information use toward business performance and the role of enviromental uncertainty and task uncertainty as a moderating variabel. The sample in this study is small businesses in Kebumen regency with 60 small businesses. Small businesses have been running for a minimum of 5 years. This study use survey method to collect the data. Moderated regression analysis (MRA) was used to test the hypothesis. The results of the study conclude that information accounting use have a significant effect to business performance. Furthermore, environmental uncertainty have no effect on the relationship between accounting information and business performance. While the task uncertainty is have a significant role as a moderating variable. Discussion of contingency theory related to small business will be explained in this study.